Physiologic Specialization of Puccinia triticina on Wheat in the United States in 2001 - Kolmer, J A (Plant disease, 2003)
Collections of Puccinia triticina were obtained from rust-infected wheat leaves by cooperators throughout the United States and from surveys of wheat fields and nurseries in the Great Plains, Ohio Valley, Gulf Coast, California, Pacific Northwest, and Atlantic Coast States in order to determine the virulence of the wheat leaf rust fungus in 2001. Single uredinial isolates (477 in total) were derived from the wheat leaf rust collections and tested for virulence phenotype on lines of Thatcher wheat that are near-isogenic for leaf rust resistance genes Lr1, Lr2a, Lr2c, Lr3, Lr9, Lr16, Lr24, Lr26, Lr3ka, Lr11, Lr17, Lr30, LrB, Lr10, Lr14a, and Lr18. The isolates also were tested for virulence on adult plants with leaf rust resistance genes Lr12, Lr13, Lr22a, Lr22b, Lr34, Lr35, and Lr37. In the United States in 2001, 44 virulence phenotypes of P. triticina were found. Virulence phenotype MBDS, which is virulent to resistance gene Lr17, was the most common phenotype in the United States. MBDS was found in the Southeast, Great Plains, and Ohio Valley regions. Virulence phenotype THBJ, which is virulent to Lr16 and Lr26, was the second most common phenotype, and occurred almost exclusively in the north-central Great Plains region. Phenotype MCDS, which is virulent to Lr17 and Lr26, was the third most common phenotype and was found primarily in the Southeast, Ohio Valley, and Great Plains regions. The Southeast and Ohio Valley regions differed from the Great Plains region for predominant virulence phenotypes, which indicate that populations of P. triticina in those areas are not closely connected. The northern and southern areas of the Great Plains region differed for phenotypes with virulence to Lr16; however, the two areas had other phenotypes in common. Virulence to the adult plant resistance genes Lr35 and Lr37 was detected for the first time in North America in the MBDS, MCJS, and MCDS phenotypes